Lived experiences of type 2 diabetes self-management in Jordan: A qualitative study of sociocultural, religious, and healthcare influences - Abdullah Hasan; Alanoud Alobaidly; Osama Alkouri; Fatma Refaat Ahmed (PLoS ONE, 2026)
Aim To explore the experiences of Jordanian adults living with T2DM and understand the influence of sociocultural, religious, emotional, and healthcare factors on their daily self-management practices. Background T2DM prevalence is alarmingly high and increasing in Jordan. However, there is a lack of understanding about the daily experiences and challenges faced by T2DM patients in the complex cultural and social environment. Understanding the experiences of T2DM patients in the complex cultural and social environment is crucial for the design and implementation of appropriate interventions. Methodology A qualitative phenomenological approach was used for the study. Semi-structured in-depth interviews were conducted with 20 participants with T2DM. Participants were selected from the major tertiary care hospital in Northern Jordan. Reflexive thematic analysis, supported by NVivo software, was used for the data analysis. Triangulation, audit trail, peer debriefing, and member checking were used for the establishment of the trustworthiness of the study. Results Six major themes were identified. Cultural pressures concerning food, challenges in adhering to the prescribed medication, religious and cultural influences, emotional and psychological burdens, gaps in healthcare services, and facilitators and coping strategies. Conclusion Self-management practices for T2DM patients in Jordan are significantly influenced by cultural, religious, emotional, and healthcare factors. Interventions for T2DM patients in Jordan need to be appropriate and tailored to the culture and community. Implications for Nursing It is the duty and responsibility of the nurse to provide appropriate education and advice based on the culture and community. Family involvement in the care process for T2DM patients in Jordan is crucial.